Daya Dukung dan Prioritas Wilayah Pengembangan Ternak Sapi Potong di Kota Tangerang Selatan - Yuniar, P. S.; Fuah, A. M.; Widiatmaka, Widiatmaka (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The objective of this studi was to determine development strategy of beef cattle based on the physical characteristics of Tangerang Selatan city. The primary data were obtained from interviews with stakeholders. Secondary data were obtained from relevant agencies and literature review. The analytical method that was used in this study was a combination of Hierarchy Analysis Procedure (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The results showed that Tangerang Selatan city has enough carrying capacity for beef cattle production based on land characteristics, suitabilities and forage carrying capacity. The priority development of beef cattle was determined based on potential and developmental direction of Tangerang Selatan city which are Pondok Aren, Ciputat, Serpong Utara and Ciputat, respectively.